Late Triassic environmental evolution in Southwestern Pangea: Plan taphonomy of the Ischigualasto Formation - Colombi, Carina Ester (2008)
The Ischigualasto Formation was deposited in a fluvial system and contains a very well preserved Triassic flora. This flora comprises seven taphofacies: (1) C(St), autochthonous silicified roots of lowstatured, woody plants associated with low-sinuosity channels and crevasse-splay deposits; (2) A(Sm/Fm), autochthonous carbonized roots or root impressions of herbaceous plants in crevasse-splay and levee deposits; (3) B(Fsm/Fm), autochthonous root halos of herbaceous plants associated with levee deposits; (4) EI(St), allochthonous silicified tree trunks and charcoal associated with high- and lowsinuosity channel bars; (5) GI(St), leaf cuticles and charcoal associated with trough cross-bedded sandstone; (6) FH(Fl/C), leaf cuticles and impressions associated with palynomorphs in abandoned-channel deposits; and (7) D(Fl), autochthonous silicified stumps in abandonedchannel deposits. Taphonomically, the Ischigualasto Formation can be divided into four parts, and these partially correspond to changes in the environment. The basal part (0–45 m) includes the transition from the underlying Los Rastros Formation and is characterized by taphofacies 1 and 2. The fluvial sediments were deposited during tectonic subsidence of the basin, resulting in development of a fluvioaxial system. The next part (45–300 m) is characterized by taphofacies 1, 2, and 3 and associated with calcic paleosols that formed under a dry seasonal climate. The middle-upper portion (300–600 m) contains all the taphofacies associated with argillic paleosols, which were formed during a time of increasing humidity. The upper portion (600–700 m) is characterized by taphofacies 1, 2, and 3, associated with immature paleosols that formed under a dry seasonal climate. The changes in humidity during deposition of the Ischigualasto Formation may have resulted from an increase in rainfall generated on the western side of Pangea by maximal development of the megamonsoon during the middle Carnian Age. The climatic signal in the Ischigualasto Formation was probably modified by the tectonosedimentary development of the basin.